An Investigation of the Relationship of ICT Access of Principals and ICT integration in Management Public Secondary Schools in Kenya - Chepkonga, Susan (International Journal for Innovation Education and Research, 2015)
The purpose of this study was to find out whether there exists a relationship between ICT access of principals and ICT integration in management of public secondary schools in Kenya. Descriptive survey design was used in Nairobi County where quantitative and qualitative research strategies were applied for the collection of data using questionnaires. The target population comprised of 75 secondary schools in Nairobi County at the time of data collection. Simple Random sampling was used to select the public secondary schools with 7(10%) principals participating in the pilot study. Data collected by questionnaires from 68 principals out of 75 principals were analyzed using Pearson’s chi square with the help of Statistical Package for Social Sciences (SPSS) programme. The findings of the analysis of data revealed that there was a significant relationship between the principals’ educational level and ICT integration in management of public secondary schools in Kenya. Out of this study recommendations were made to the county government and secondary schools in Nairobi County and Kenya in general.